Arabic Language Learning Innovation through Interactive Design in Canva: Case Study at STAI Auliaurrasyidin Campus, Indragiri Hilir Regency, Riau - Nurlatipah, Nurlatipah; Zahrah, Humairatuz; Hasaniyah, Nur; Anshory, Abdul Muntaqim Al (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
The trend of Arabic language learning needs today cannot be separated from the use of interactive technology-based multimedia, one of which is the Canva application, where lecturers can design Arabic language learning accompanied by video, sound, animation so that students are highly enthusiastic about the material provided. The purpose of this study is to investigate how the use of canva interactive design as an innovation in Arabic language learning at STAI Auliaurrasyidin Campus and the results of utilizing canva-based technology media for lecturers and students. This research uses a qualitative approach with a case study research type and is descriptive in nature. Data collection techniques were carried out by means of observation and interviews. The research findings show that the Canva media used by lecturers has many features that help in the design of interactive Arabic language materials in class, such as making mufradat cards, making mufradat learning videos with Canva, and making online presentations via the Web. Some of the obstacles in using design in Canva are that educators still do not know how to create designs to make them look attractive, lack of stable signal when designing lessons, and limited infrastructure in applying interactive video media Canva. The way to overcome the obstacles is to hold socialization such as workshpp on the use of canva interactive media for all educators as a learning innovation. Furthermore, the use of canva media encourages the motivation and learning outcomes of students.